Kill your radio a podcast production featuring selected independent musicians from Davao City - Ledesma, Dranessa Precious Claire T.
The production of Kill Your Radio podcast served as an alternative media in promoting Davao independent music. The episodes were based on the 5 assumptions of the Uses and Gratifications Communication theory by E. Katz, J. Blumler, and M. Gurevitch. Podcast principles by Andrew Middleton, Tee Morris, and Evo Terra were also applied in the whole production of the episodes. It took 4 weeks to complete the whole creative process of the production of the 2 episodes. Two podcast episodes with different program designs were made. The program designs aimed to portray the ?rawness? and independence of the Davao musicians and to popularize Podcasting as a new and alternative media that could promote independent music. Overall, the production of the two episodes was successful. The proponent was able to get impressions and comments from people about the podcast site and episodes.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts